2002
DOI: 10.1200/jco.20.4.937
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of Weekly Paclitaxel in Patients With Previously Treated Advanced Urothelial Cancer

Abstract: Although the overall response rate to weekly paclitaxel in patients with previously treated advanced urothelial cancer was modest, the chemotherapy-refractory nature of the study population should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(88 citation statements)
references
References 18 publications
1
85
0
2
Order By: Relevance
“…Paclitaxel alone yields a 42% response rate against urothelial carcinoma when used as a first-line treatment, 17 but yields only a 10% response rate in patients who were treated previously. 18 Considering the low response rate of paclitaxel alone when used as a second-line treatment, its combination with gemcitabine, cisplatin, carboplatin and ifosfamide have been investigated , and the response rate increased to 15-40%. 1,[9][10][11][12][13]18,19 In the present study, the response rate was 19.0% and overall disease control rate was 42.9%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paclitaxel alone yields a 42% response rate against urothelial carcinoma when used as a first-line treatment, 17 but yields only a 10% response rate in patients who were treated previously. 18 Considering the low response rate of paclitaxel alone when used as a second-line treatment, its combination with gemcitabine, cisplatin, carboplatin and ifosfamide have been investigated , and the response rate increased to 15-40%. 1,[9][10][11][12][13]18,19 In the present study, the response rate was 19.0% and overall disease control rate was 42.9%.…”
Section: Discussionmentioning
confidence: 99%
“…For previous chemotherapy, 18 patients received the GC regimen as the first-line and the M-VAC regimen as the second-line treatments, and three patients received M-VAC as the first-line and GC as the second-line treatments. The median treatment-free interval was 3.5 months (range [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The response rate including complete remission (CR) and PR of the previous two regimens was 38.1%.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…The overall response rate was 69%, with 41% complete responses. Despite the encouraging activity, the authors recommended against further use of this dose and schedule given the high rate of pulmonary toxicity (14% grade [3][4][5]. This excessive rate of pulmonary toxicity was not encountered in the other trials of gemcitabine and paclitaxel using different doses and schedules.…”
Section: Paclitaxel Plus Gemcitabinementioning
confidence: 99%
“…Multiple trials have evaluated single-agent paclitaxel in metastatic TCC [2][3][4][5]. In an Eastern Cooperative Oncology Group (ECOG) trial, 26 previously untreated patients received paclitaxel 250 mg/m 2 by 24-hour continuous infusion every 21 days with granulocyte colony-stimulating factor (GCSF) support [4].…”
Section: Paclitaxelmentioning
confidence: 99%
“…In this setting, it has achieved an ORR of 22.5% and an mOS of 5 months [58]. Taxanes, including paclitaxel, nab-paclitaxel and docetaxel, have established activity for these patients, with ORRs ranging from 10 to 28% and including several durable responses [59][60][61][62]. The nontaxane microtubule modulator eribulin has more recently been evaluated in a single-arm, Phase II study that included treatment-naive patients as well, and showed an ORR of 32% with an mOS of 9.6 months (for second line or beyond and taxane-naive ORR was 28%, mOS 9.6 months) [63].…”
Section: Systemic Therapy For Metastatic Diseasementioning
confidence: 99%